ظاهرة الترادف في تفسير الكشاف للزمخشري The Features of aesthetical and aymmetrical aynonyms in tafsir Al-Khashaf: analytical and descriptive discourse (2018)
Apparently, Tafsir Al-Khashaf authored by Jarullahi Az- Zamakhashari (476-538 A.H) is regarded as one of the major source of Arabic literary arts, in having full acquaintance of the Holy Qur’an, Arabic Rhetoric, Grammar, Stylistic; in addition to its religious embellishment. However, the influence and impacts of this book among the scholars in Arabo-Islamic countries cannot be under-estimated which led to its peculiarities and merits by studying it from religious and literary context: Grammatical, Stylistic, Rhetorical etc. Despite the multiplicity of the books written by Zamakhshari, Al-Khashaf is regarded as most populous book in Arabo-Islamic countries. On this, Ibn Khalidun asserts that; “What many Quranic Interpreters did not treated on Al-Bayan Rhetoric before the emergence of Jarullahi Zamakhashari, was treated in Al-Khashaf. He (Zamakhshari) puts his book down on Quranic exegesis, treated Quranic verses with their rules in (Bayan) while others neglected it. The researcher discovers that the book serves as a compendium for the students and readers because of aesthetical and symmetrical synonyms and other literary features circumvented. Therefore, this paper is aiming to study the features of aesthetical and symmetrical synonyms in Al-Khashaf Exegesis. Before delving in to main work, the concept of Synonyms; the views of Scholars on its acceptance and rejection and the causes and conditions stated for synonyms in Arabic studies would be discussed, likewise, short biography of Zamakhshari and his methods in his book understudy would be showcased. The researcher applies analytical and descriptive method in this work.